Influence of academic stress on prevalence and susceptibility to depression among Obafemi Awolowo University students, Ile-Ife, Nigeria - Dada, Deborah; Olatomide, Onijuni Olufemi; Adeniyi, Rosemary Alaba (Journal of Advanced Guidance and Counseling, 2025)
Purpose – The study investigated the prevalence of students’ susceptibility to depression in Obafemi Awolowo University. It also investigated the extent to which academic stress could predict students’ susceptibility to depression. Method – The population for this study consisted of undergraduate students of Obafemi Awolowo University, Ile-Ife.  A sample size of 612 undergraduate students was selected using multi-stage sampling procedure. In the first stage, six faculties out of thirteen were randomly selected, using systematic sampling technique. In the second stage, three departments were selected randomly from each of the six faculties, using simple random sampling technique to give a total of 18 departments. In the third stage, accidental sampling technique was used to select 34 students from each of the three departments selected in faculties to make a total of 612 respondents. Data collected were analysed, using frequency counts, percentages and Simple Linear Regression analysis. Result – The results showed that 20.4% of the students had mild susceptibility to depression, 51.5% had moderate susceptibility to depression, while 28.1% had severe susceptibility to depression. The results further showed that 12.6% of the respondents had mild stress from their academics, majority 73.9% had moderate stress from their academics while 13.6% had extreme stress from their academics. In addition, the result reveals that academic stress significantly predict student’s susceptibility to depression at (p<0.05). Implication – The study provides useful evidence that can inform policymakers, counsellors, and universities to develop effective mental health interventions by determining the factors that lead to the psychological distress of students. Originality/Value – The study is important since it offers empirical evidence into the nature and prevalence of depressive symptoms in university students which can be easily ignored in spite of their increased vulnerability to it. *** Tujuan – Studi ini menyelidiki prevalensi kerentanan mahasiswa terhadap depresi di Universitas Obafemi Awolowo. Studi ini juga menyelidiki sejauh mana stres akademik dapat memprediksi kerentanan mahasiswa terhadap depresi. Metode – Populasi studi ini terdiri dari mahasiswa sarjana Universitas Obafemi Awolowo, Ile-Ife. Sebanyak 612 mahasiswa sarjana dipilih menggunakan prosedur sampling bertahap. Pada tahap pertama, enam fakultas dari total 13 fakultas dipilih secara acak menggunakan teknik sampling sistematis. Pada tahap kedua, tiga departemen dipilih secara acak dari masing-masing enam fakultas menggunakan teknik sampling acak sederhana, sehingga totalnya menjadi 18 departemen. Pada tahap ketiga, teknik sampling acak digunakan untuk memilih 34 mahasiswa dari masing-masing tiga departemen yang dipilih di fakultas, sehingga total responden menjadi 612. Data yang dikumpulkan dianalisis menggunakan hitung frekuensi, persentase, dan analisis regresi linier sederhana. Hasil – Hasil menunjukkan bahwa 20,4% mahasiswa memiliki kecenderungan depresi ringan, 51,5% memiliki kecenderungan depresi sedang, sementara 28,1% memiliki kecenderungan depresi berat. Hasil lebih lanjut menunjukkan bahwa 12,6% responden mengalami stres ringan akibat akademik, mayoritas 73,9% mengalami stres sedang akibat akademik, sementara 13,6% mengalami stres ekstrem akibat akademik. Selain itu, hasil menunjukkan bahwa stres akademik secara signifikan memprediksi kerentanan mahasiswa terhadap depresi (p<0,05). Implikasi – Studi ini menyediakan bukti yang berguna bagi pembuat kebijakan, konselor, dan universitas untuk mengembangkan intervensi kesehatan mental yang efektif dengan menentukan faktor-faktor yang menyebabkan gangguan psikologis pada mahasiswa. Orisinalitas/Nilai – Studi ini penting karena menyediakan bukti empiris tentang sifat dan prevalensi gejala depresi pada mahasiswa universitas, yang sering diabaikan meskipun mereka memiliki kerentanan yang meningkat terhadapnya.